2008
DOI: 10.1080/09537100701210057
|View full text |Cite
|
Sign up to set email alerts
|

Increased platelet activation markers in rheumatoid arthritis: Are they related with subclinical atherosclerosis?

Abstract: Atherosclerotic cardiovascular mortality is increased in rheumatoid arthritis (RA) patients. We evaluated the association of inflammatory response with platelet, endothelial, coagulation activation parameters; and subclinical atherosclerosis in RA patients. We included 27 RA patients (21 female; six male) and 19 healthy subjects (14 female; five male). Disease activity score (DAS28) in RA patients was calculated; and patients were divided into two groups as active and inactive. Flow cytometry was used to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 36 publications
1
50
1
Order By: Relevance
“…As shown in Table 3, there was not significantly change in the concentration of Hb and WBC number from different TPs-treated rats compared with the normal and H 2 O-treated groups. However, compared with the normal rats, the RBC number decreased significantly, in contrast, the platelet (PLT) number increased significantly, which are commonly found in RA patients (Vreugdenhil and Swaak, 1990;Pamuk et al, 2008). With TPs treatment, the decreased number of RBC not only increased but also restored to the nearly normal level in TP-C and TP-Dtreated rats, and PLT number decreased significantly in TP-C and TP-D treatment to nearly normal levels in vivo (Table 3).…”
Section: Effects Of Tps On Complete Blood Count In Cia Ratsmentioning
confidence: 94%
See 1 more Smart Citation
“…As shown in Table 3, there was not significantly change in the concentration of Hb and WBC number from different TPs-treated rats compared with the normal and H 2 O-treated groups. However, compared with the normal rats, the RBC number decreased significantly, in contrast, the platelet (PLT) number increased significantly, which are commonly found in RA patients (Vreugdenhil and Swaak, 1990;Pamuk et al, 2008). With TPs treatment, the decreased number of RBC not only increased but also restored to the nearly normal level in TP-C and TP-Dtreated rats, and PLT number decreased significantly in TP-C and TP-D treatment to nearly normal levels in vivo (Table 3).…”
Section: Effects Of Tps On Complete Blood Count In Cia Ratsmentioning
confidence: 94%
“…As PLT is considered as an activator in inflammation and pathogenesis of RA (Milovanovic et al, 2004;Pamuk et al, 2008;Matowicka-Karna et al, 2013), indicating that TP-C and TP-D could restore PLT number to nearly normal level, which might be benefit for reducing inflammation. These results suggested that four tested TPs have little affect for Hb concentration and WBC number, but TP-C and TP-D show advantage of RA treatment via restoring PLT and RBC number to normal level as well as inhibition of inflammation simultaneously in vivo.…”
Section: Effects Of Tps On Complete Blood Count In Cia Ratsmentioning
confidence: 98%
“…By using different animal models, studies have shown the indispensable role of platelets in the initiation and progression of inflammatory and autoimmune diseases, including sepsis, 12 atherosclerosis, 13 autoimmune myocarditis, 14 systemic lupus erythematosus, 15 rheumatoid arthritis [16][17][18][19] and so on. Allergic asthma is a chronic inflammatory pathological condition with critical involvement of T helper 2 (Th2) cells that is harmful to human health throughout the world.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, there has been no study evaluating PMC and PNC in AS. Some studies reported that PMC and PNC were elevated in RA [11,21]. Until a short time ago, the gold standard for platelet activation was accepted to be P-selectin expression; but, it was shown that degranulated platelets lost surface P-selectin [19].…”
Section: Discussionmentioning
confidence: 97%